Analysing online discussions in educational and work based settings - Blake, Canan; Scanlon, Eileen (Proceedings of the International Conference on Networked Learning, 2014)
Networked learning is becoming more and more about connectivity of learners or professionals and connectivity to resources available online and sometimes freely. Researchers are making use of these by designing online environments where this notion of connectivity and vast resources available to learners can be exploited. Many online discussion tools are available for use in educational settings. This paper discusses means of comparing the quality of interaction in these tools. We focus on the use of an online discussion tool called InterLoc (http://www.interloc.org.uk/). InterLoc is based on research by McAlister (2004) who designed a tool for online peer discussion that guides students' dialogue towards more academic interactions and facilitates extended argument. A significant feature of the design of the tool is managed synchronous dialogue e.g. the use of sentence openers, and the facility to reply to earlier contributions. The design features of InterLoc ensure that it provides a collaborative argumentation environment for learners in higher education. We also demonstrate that it is possible to structure argumentation using InterLoc in different settings, both academic and work-place. One of our case studies was carried out with postgraduate distance learning students studying science communication and the participants were asked to consider the idea that everyone's DNA should be kept on a data base to help fight crime. The second case study was in a health and social care setting and the participants were family-support workers of a London based charity, supporting families and individuals offering practical, emotional and financial help. They were asked to consider the case of a severely obese child whom social services are considering taking into care as the parents are unable to control his eating. The participants discussed what would be the best for the child. We used two methods of comparing the quality of interaction in these sessions: We analysed the transcripts of discussion sessions using content analysis and frequency of sentence openers and compared these analyses with those using Toulmin's Argumentation Pattern (TAP). By comparing the results of these two analyses, we explored the possibility of using these measures as an indicator of the quality of the discussion taking place. Our findings have confirmed the potential of the InterLoc sentence opener analyses for future work.